MOTIVASI ORANGTUA MEMILIH BIMBINGAN BELAJAR OMAR PEKANBARU DI KOTA PEKANBARU - Hasimah, Putri; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The parents enthusiasts of making their children succed in education were so big, they were racing and competing among them to choose and send their children to the best non formal education institution or simply a private course. The rapid growth of private courses in Pekanbaru city was caused by the high response and willingness of parents to send their children to study in a private course. Parents enthusiasts were bigger than their children enthusiasts in joining and studying in a private course, rarely the willingness and intention of studying in a private course purely came from the children because most of them were forced by their parents. The purpose of this study was to find out the parents characteristics and their motivation in choosing Omar Pekanbaru course as the nonformal educational institution to help their children in learning. This study applied descriptive qualitative analysis approach, which the number of the sample was 10 persons that were chosen by using purposive sampling method. They were parents who had chosen and sent their children to Omar Pekanbaru course for the last two years. The finding of the study indicated thet parents motivation to send their children in Omar Pekanbaru course consisted of intrinsic motivation and extrinsic motivation and their characteristics were different in terms of their profession, educational background, income, family member, and tribe.Keyword : parents, motivation, characteristics